Chapter Massimo Quaini e il viaggio: il ruolo della verticalità - Greppi, Claudio (Territori, 2021)
In the issue of Geotema dedicated to travel ("Travel as source of geographical knowledge"), in 1997, Massimo Quaini's article topic was "The geographical invention of verticality: for the history of the 'discovery' of mountains". It concerns a fundamental segment of the history of geographical knowledge, between eighteenth and nineteenth centuries, involving both the Old and New World: Saussure in the Alps and Humboldt in the Andes. He had already worked on this same topic in other occasions, investigating institutions like CAI in Italy, and mountain's role in the 'official' geography. Such lectures mark a path that, I think, finds a theoretical output in 2006 Parma conference, dedicated to the "end of the travel", where Quaini spoke about "Between Eighteenth and Nineteenth Century: the travel and the new paradigm of geography": a rich and problematic lecture, opening to further researches. But perhaps before this point of arrival, the new paradigm, I would suggest to think on an idea offered by the Geotema article, where we read: "so, if we want to fully speak of discovering the mountains it will be necessary that the culture of the outside travellers meet that of the mountaineers". Actually, in Quaini's last lecture I take into consideration, the one at Forte di Bard in September 2006, his attention shifts definitely on the figures of alpine travellers, who may encounter knowledge acquired from local culture.